1993
DOI: 10.1007/bf02641001
|View full text |Cite
|
Sign up to set email alerts
|

Soap determination in sewage sludge by high‐performance liquid chromatography

Abstract: A specific analytical method for soaps in the environment has been developed. Three main steps are involved in the process: (i) removal of fatty materials (lipids) other than soaps; (ii} derivatization of soaps with either bromomethyl-methoxy-coumarin or p-bromo phenacyl bromide to get a suitable response by ultraviolet; and (iii) separation of different carbon-chain fatty soaps by highperformance liquid chromatography, followed by either ultraviolet or fluorometry detection. The method has been applied succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…While the Ca-soaps (C 12 , C 18 , C 22 ) exhibited high gas formation rates (> 85%) in the static system within a 10-day test duration, the semi continuously run investigations with Na-soaps showed that the time needed for mineralization was increasing with the chain length and concomitantly with the water solubility. The relatively poor water solubility of Ca/Mgsoaps may also account for the high soap concentrations found in the raw sludges of sewage treatment plants (up to 5% of sludge dry matter); nevertheless, the mass balances of soap based on a monitoring study of the concentrations in sludges of a digester influent and effluent, respectively, showed unequivocally that the removal of soap was about 70% 64) .…”
mentioning
confidence: 99%
“…While the Ca-soaps (C 12 , C 18 , C 22 ) exhibited high gas formation rates (> 85%) in the static system within a 10-day test duration, the semi continuously run investigations with Na-soaps showed that the time needed for mineralization was increasing with the chain length and concomitantly with the water solubility. The relatively poor water solubility of Ca/Mgsoaps may also account for the high soap concentrations found in the raw sludges of sewage treatment plants (up to 5% of sludge dry matter); nevertheless, the mass balances of soap based on a monitoring study of the concentrations in sludges of a digester influent and effluent, respectively, showed unequivocally that the removal of soap was about 70% 64) .…”
mentioning
confidence: 99%
“…Calcium soap (50 g/kg) and a mixture of free fatty acids containing 100 g/kg of each fatty acid were added to samples to optimize a procedure for interference removal. First, the solvent was selected following the methodology proposed by Moreno et al [17]. We tested petroleum ether, hexane, cyclohexane, ethyl acetate, and methanol.…”
Section: Resultsmentioning
confidence: 99%
“…Commercial fatty acids C 10:0 to C 18:1 (purity 97-99%) were supplied by Merck. Fatty acid K and Ca salts were synthesized in our laboratory (purity 98-99%) following the methodology proposed by Moreno et al [17]. Briefly, individual solutions of fatty acids with chain length from C 8:0 to C 20:0 in acetone were prepared (100 g/L), and K soap was obtained by precipitation with a saturated water solution of potassium carbonate.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty acid potassium and calcium salts were synthesized in our laboratory (purity 98-99%) following the methodology proposed by Moreno. [18] Commercial LAS was supplied by Cepsa Quimica S.A. (San Roque, Spain) as an aqueous solution of the sodium salt with a LAS content of 47.5% (w/w). Average molecular weight was 342.2 g mol −1 and the distribution of the linear alkyl chain homologues was: C 10:0 13.5%, C 11:0 33.1%, C 12:0 29.3%, C 13:0 23.1% and others 1%.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%